The Power of a Good Story: Narrative Persuasion in Extremist Propaganda and Videos against Violent Extremism - Bente, Gary (International journal of conflict and violence, 2018)
The perceived threat of extremist online propaganda has generated a need for countermeasures applicable to large audiences. The dissemination of videos designed to counter violent extremism (CVE videos) is widely discussed. These videos are often described as “counter-narratives,” implying that narrativity is a crucial factor for their effectiveness. Experimental research testing this assumption is rare and direct comparisons of narrativity effects between propaganda and CVE videos are lacking. To fill this gap, we conducted two experiments (one in a laboratory and one online) in which we confronted German participants with different religious affiliations and from various cultural backgrounds (NStudy 1 = 338 and NStudy 2 = 155) with Islamist extremist or right-wing extremist propaganda videos and with corresponding CVE videos. The results confirmed that narrativity (a) increases persuasive processing of propaganda and CVE videos, (b) fosters amplification intentions regarding these videos, and (c) increases attraction to extremists versus counter-activists. Thus, our studies highlight the crucial role of narrativity in both extremist propaganda and video-based CVE approaches